Design and Measurements of Rectangular Dielectric Resonator Antenna Linear Arrays - Feras Z. Abushakra; Asem S. Al-Zoubi; Derar F. Hawatmeh, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, two, four, eight and sixteenelement Rectangular Dielectric Resonator Antenna (RDRA) linear arrays fed by microstrip line have been designed and simulated. The DRA is excited by a vertical strip placed on the middle of the DRA wide side wall through a coaxial probe attached to the microstrip line on the other side of the substrate. The ground plane is sitting directly underneath the RDRA while the microstrip line feeder is at the opposite side of the substrate to avoid the unwanted radiation from the feeder. The simulated and measured 10 dB return loss bandwidth of the antenna arrays are 67.8%, 75%, 73.5%, and 76% for the two, four, eight and sixteen-element arrays respectively. The simulated gain of the single element antenna is about 6 dBi, while it reaches to about 17 dBi for the 16-element array.